A Study to Assess the Caregiver Burden of the Caregivers of PostOperative Patients with Oral Cancer in B.R.A Institute Rotary Cancer Hospital, All India Institute of Medical Sciences, New Delhi - Paulose, Neenumol; Prashant Sinha, Aditi; V. S. Deo, S. (International Journal of Nursing Research, 2023)
Introduction: Cancer is a leading cause of death in both developed and underdeveloped countries. The Indian subcontinent accounts for one-third of the world burden of head-and-neck cancer. Caregivers of patients with oral cavity cancer experience heavy burden during and post-treatment period, which, in turn, may affect the caregiver’s ability. Aim: This study aims to assess the caregiver burden (CB) of the caregivers of post-operative oral cancer patients. Methodology: The study was conducted at AIIMS, New Delhi. The data were collected by convenience sampling from 50 caregivers of the post-operative patients with oral cancer during June 2017 to December 2017. Self-developed CB assessment questionnaire was used to assess the perceived level of the CB during hospital stay and at 1 month follow-up. Ethical clearance was obtained from the Institutional Ethics Committee. Results: Half of the caregivers were male and half were female. Majority of the caregivers always perceived physical problem (70%, 55.8%), emotional problem (60%, 52.9%), logistical problem (64%, 55.88%), inadequate knowledge and skill (66%, 64.7%), and socioeconomic problem (56%, 73.5%) during hospital stay and 1 month follow-up, respectively. There was a significant decrease in the overall CB at 1 month follow-up (17.16 ± 8.19 and 14.96 ± 9.87) (P = 0.04). Conclusions: Reduction in CB was noted over the month. Future studies with larger sample over extended period will yield much.